Protease-mediated activation of Par2 elicits calcium waves during zebrafish egg activation and blastomere cleavage. - Jiajia Ma; Tom J Carney (PLoS Biology)
Successful initiation of animal development requires activation of the egg immediately prior to fusion of gamete pronuclei. In all taxa, this is initiated by waves of calcium transients which transverse across the egg. Calcium waves also occur at cleavage furrows during later blastula cytokinesis. Calcium is released from the endoplasmic reticulum through activation of inositol-1,4,5-trisphosphate (IP3) receptors. Only a subset of the mechanisms employed to generate IP3 during vertebrate egg activation are defined, with strong evidence that other critical mechanisms exist. Serine proteases have been long implicated in egg activation and fertilization. Here, we report that treatment of zebrafish eggs with serine protease inhibitors leads to defective calcium wave propagation and failed egg activation. We further show that mutation of zebrafish Protease-activated receptor 2a (Par2a) also results in severe disruption of egg activation, leading to failed chorion elevation and ooplasmic segregation. Milder par2a mutants progress further, but then show abnormal blastomere cleavage. We observed that par2a mutants show decreased amplitude and duration of calcium transients. Restoring Ca++ or direct injection of IP3 ligand rescues egg activation aborted by either serine protease inhibitor treatment or by mutation of Par2a. We thus show that serine protease activity is a critical regulator of IP3 and subsequent calcium wave amplification during zebrafish egg activation, and link this to intracellular calcium release via the protease receptor, Par2a. This constitutes a novel signaling pathway critical for successful fertilization.